EZH2 inhibition promotes epithelial-to-mesenchymal transition in ovarian cancer cells - Cardenas, Horacio (Oncotarget, 2016)
Cancer cells acquire essential characteristics for metastatic dissemination through the process of epithelial-to-mesenchymal transition (EMT), which is regulated by gene expression and chromatin remodeling changes. The enhancer of zeste homolog 2 (EZH2), the catalytic subunit of the polycomb repressive complex 2 (PRC2), catalyzes trimethylation of lysine 27 of histone H3 (H3K27me3) to repress gene transcription. Here we report the functional roles of EZH2-catalyzed H3K27me3 during EMT in ovarian cancer (OC) cells. TGF-β-induced EMT in SKOV3 OC cells was associated with decreased levels of EZH2 and H3K27me3 (P<0.05). These effects were delayed (~72 h relative to EMT initiation) and coincided with increased (>15-fold) expression of EMT-associated transcription factors ZEB2 and SNAI2. EZH2 knockdown (using siRNA) or enzymatic inhibition (by GSK126) induced EMT-like changes in OC cells. The EMT regulator ZEB2 was upregulated in cells treated with either approach. Furthermore, TGF-β enhanced expression of ZEB2 in EZH2 siRNA- or GSK126-treated cells (P<0.01), suggesting that H3K27me3 plays a role in TGF-β-stimulated ZEB2 induction. Chromatin immunoprecipitation assays confirmed that TGF-β treatment decreased binding of EZH2 and H3K27me3 to the ZEB2 promoter (P<0.05). In all, these results demonstrate that EZH2, by repressing ZEB2, is required for the maintenance of an epithelial phenotype in OC cells.